Eosinophils in Fungus-Associated Allergic Pulmonary Disease - Ghosh, Sumit; Hoselton, Scott A.; Dorsam, Glenn P.; Schuh, Jane M. (Frontiers in Pharmacology, 2013)
Asthma is frequently caused and/or exacerbated by sensitization to fungal allergens, which are ubiquitous in many indoor and outdoor environments. Severe asthma with fungal sensitization is characterized by airway hyperresponsiveness and bronchial constriction in response to an inhaled allergen that is worsened by environmental exposure to airborne fungi and which leads to a disease course that is often very difficult to treat with standard asthma therapies. As a result of complex interactions among inflammatory cells, structural cells, and the intercellular matrix of the allergic lung, patients with sensitization to fungal allergens may experience a greater degree of airway wall remodeling and progressive, accumulated pulmonary dysfunction as part of the disease sequela. From their development in the bone marrow to their recruitment to the lung via chemokine and cytokine networks, eosinophils form an important component of the inflammatory milieu that is associated with this syndrome. Eosinophils are recognized as complex multi-factorial leukocytes with diverse functions in the context of allergic fungal asthma. In this review, we will consider recent advances in our understanding of the molecular mechanisms that are associated with eosinophil development and migration to the allergic lung in response to fungal inhalation, along with the eosinophil’s function in the immune response to and the immunopathology attributed to fungus-associated allergic pulmonary disease.